2017
DOI: 10.1038/s41477-017-0035-3
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptome dynamics revealed by a gene expression atlas of the early Arabidopsis embryo

Abstract: During early plant embryogenesis, precursors for all major tissues and stem cells are formed. While several components of the regulatory framework are known, how cell fates are instructed by genome-wide transcriptional activity remains unanswered - in part because of difficulties in capturing transcriptome changes at cellular resolution. Here, we have adapted a two-component transgenic labelling system to purify cell type-specific nuclear RNA and generate a transcriptome atlas of early Arabidopsis embryo devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 75 publications
5
95
0
Order By: Relevance
“…At this stage the outer cells acquire protoderm identity (Abe et al, 2003) and we find that the inner cells express multiple vascular marker genes, identifying these cells as the first with vascular attributes. These findings are in line with results of a recent transcriptome study which found that the transcriptome of these (inner) cells is similar to that of the later vascular cells (Palovaara et al, 2017). No ground tissue markers have so far been found to be present in the inner lower tier cells (unpublished).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…At this stage the outer cells acquire protoderm identity (Abe et al, 2003) and we find that the inner cells express multiple vascular marker genes, identifying these cells as the first with vascular attributes. These findings are in line with results of a recent transcriptome study which found that the transcriptome of these (inner) cells is similar to that of the later vascular cells (Palovaara et al, 2017). No ground tissue markers have so far been found to be present in the inner lower tier cells (unpublished).…”
Section: Discussionsupporting
confidence: 89%
“…The route to a vascular-specific expression pattern starts in the 16-cell stage embryo rather than at early globular stage as previous reports have suggested. In previous work, inner lower tier cells at 16-cell stage were shown to resemble their vascular daughter cells at the globular stage using GO term enrichment in transcriptomes (Palovaara et al, 2017) . Indeed, we find that many vascular marker genes start expression at 16-cell stage, where they are exclusively expressed in the inner cells: DOF6, IQD15, PEAR1, SOK1, WOL and ZLL ( Figure 1A).…”
Section: Establishment Of Vascular Tissue Identity Is a Multi-step Prmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas the embryo proper undergoes many developmental and morphological changes to eventually become the mature embryo within the seed, the suspensor is a terminally differentiated embryo region that degenerates as the embryo matures. Several studies have shown that different genes are expressed in the embryo proper and suspensor (4)(5)(6)(7)(8), but how these genes are organized into regulatory networks (9) operating in the different embryo regions remains unknown.…”
Section: Introductionmentioning
confidence: 99%